(untitled) (Progressive Agriculture, 2018)
The experiment was at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh–2202 during late Rabi season (December-March) of 2015. It was two factorial experiment (1) irrigation level and (2) nitrogen rate. Irrigation significantly influenced on yield and yield contributing characters except harvest index. The highest plant height (79.69cm), maximum number of total tillers plant-1 (4.725), number of grains spike-1 (40.61), spike length (11.80cm), 1000 grain weight (28.67g), grain yield (3.227 t ha-1), harvest index (41.26%) were obtained by mulching treatment. Nitrogen rate significantly influenced the yield and yield contributing characters. The highest plant height (80.37cm), maximum number of total tillers plant-1 (5.124), number of grains spike-1 (40.85), spike length (10.37cm), 1000 grain weight (31.86g), grain yield (3.792 t ha-1), harvest index (41.69%) were obtained by the application of 180 kg N ha-1. The combined effect of Irrigation and nitrogen significantly interacted on yield and yield contributing characters. The highest plant height (83.44cm), number of total tillers plant-1 (5.66), number of grains spike-1 (41.60), 1000 grain weight (36.66g), grain yield (4.32 t ha-1) and harvest index (47.36%) were obtained by application of 180 kg N ha-1 with mulching. The present study revealed that high dose of nitrogen 180 kg ha-1 and mulching practice can compensate low production of wheat even at late sowing. Progressive Agriculture 29 (3): 213-220, 2018